Cardamonin Ameliorates Insulin Resistance Induced by High Insulin and High Glucose through the mTOR and Signal Pathway - Niu, Peiguang; Zhang, Yuxuan; Shi, Daohua; Chen, Yaoyao; Deng, Jie (Planta Medica, 2013)
The mammalian target of rapamycin is crucial in the regulation of cell growth and metabolism. Recent studies suggest that the mammalian target of rapamycin and its downstream 70-kDa ribosomal S6 kinase 1 negatively modulate the insulin-signaling pathway, which is considered the main cause of insulin resistance. The aim of this study is to investigate the effects of cardamonin, a potential inhibitor of the mammalian target of the rapamycin, on insulin-resistant vascular smooth muscle cells and the molecular mechanisms involved. Vascular smooth muscle cells were cultured with high glucose and high insulin to induce insulin resistance. The mammalian target of rapamycin was overstimulated in cells that were incubated with high glucose and high insulin, as reflected by the excessive activation of S6 kinase 1. Insulin-resistant vascular smooth muscle cells displayed hyperphosphorylation of insulin receptor substrate-1 at Ser residues 636/639, which decreased the activity of insulin receptor substrate-1. Also, the activation of protein kinase B and phosphorylation of glycogen synthesis kinase-3β were inhibited. Cardamonin increased the 2-deoxyglucose uptake and glycogen concentration, which was reduced by insulin resistance. As with rapamycin, cardamonin inhibited the activity of the mammalian target of rapamycin and S6 kinase 1, decreased the Ser 636/639 phosphorylation of insulin receptor substrate-1 and increased the activation of protein kinase B. Both of them increased the Ser9 phosphorylation of glycogen synthesis kinase-3β and decreased the expression of glycogen synthesis kinase-3β. However, neither cardamonin nor rapamycin increased the expression of glucose transport 4 which decreased in insulin-resistant vascular smooth muscle cells. This study suggests that cardamonin inhibited the activity of the mammalian target of rapamycin and eliminated the negative feedback of the mammalian target of rapamycin and S6 kinase 1 on the insulin-signaling pathway.
Keywords: cardamonin; mTOR; insulin resistance; VSMCs; glucose metabolism; IRS-1; S6K1